2012
DOI: 10.1089/end.2011.0592
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcomes and Cost Assessment Between Bipolar Versus Monopolar Transurethral Resection of the Prostate

Abstract: Purpose: We compared the in-hospital outcomes between bipolar and monopolar transurethral resection of the prostate (B-TURP and M-TURP, respectively) on a real-world practice using a large database. Patients and Methods: Patients who underwent TURP were extracted from the Diagnosis Procedure Combination database, which is a case-mix administrative claims database in Japan. TURP procedures were classified into M-TURP and B-TURP groups according to intraoperative use or nonuse of D-sorbitol solution, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…These results are consistent with the study conducted by Sugihara et al. who reported 20/1531 (1.3%) patients undergoing B‐TURP and 118/5155 (2.3%) patients undergoing M‐TURP required homologous blood transfusion. Clot retention was relatively more common in patients undergoing M‐TURP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with the study conducted by Sugihara et al. who reported 20/1531 (1.3%) patients undergoing B‐TURP and 118/5155 (2.3%) patients undergoing M‐TURP required homologous blood transfusion. Clot retention was relatively more common in patients undergoing M‐TURP.…”
Section: Discussionsupporting
confidence: 92%
“…Sugihara et al. reported that 16/5155 (0.03%) participants developed TUR syndrome in their database study. When excluding the trial undertaken by Yousef et al.…”
Section: Discussionmentioning
confidence: 98%
“…The duration of hospitalization was recognized as a significant contributor to the cost of TURP (19). In fact, as demonstrated by Goh and Gonzalez and by Sugihara et al (20,21), the impact of prolonged hospitalization can be more important than the type of treatment modality on cost savings. The study by Shum et al reported a 45.6% reduction in bill size if hospital stay was reduced from 3 days to 2 days in their center (22).…”
Section: Discussionmentioning
confidence: 99%
“…The company identified three economic studies [ 39 41 ], and the EAC identified one additional study, which included an economic estimation [ 36 ], but these were not used as evidence for TURis by the company or by the EAC, because of low applicability to the scope.…”
Section: Review Of Clinical and Economic Evidencementioning
confidence: 99%